Audit rotation and audit fee determination policy on audit quality with lowballing audit practice as the intervening variable - Anisa Listya; Muhammad Ichsan Siregar (Jurnal Akuntansi, Keuangan, dan Manajemen, 2020)
Purpose: This study aimed to analyze the effect of audit rotation and audit fee policy toward audit quality with lowballing audit practice as the intervening variable. Research methodology: The research method used was path analysis with a sample of twenty manufacturing companies in Indonesia Stock Exchange during 2015-2019. Results: The research results prove that the audit rotation and audit fee policy significantly affect the audit quality through the lowballing audit. Limitations: The research sample used manufacturing companies listed on the IDX, so the generalization of this study's results for non-manufacturing and non-listed companies must be made carefully. Contribution: This research can provide benefits for Audit Firms, regulators (PPPK), and professional associations (IAPI) as an evaluation of the implementation of audit rotation policies, implementation of regulations for determining audit fees following IAPI's Regulation No. 2 of 2016 concerning Determination of Financial Report Audit Service Fees, as well as evaluation of the implementation of the audit quality indicator guidelines formulated by IAPI. Keywords: Audit rotation, Policy of determining audit fee, Lowballing audit, Negative abnormal audit fee, Audit quality